Perovskite Solar Cells: Can We Go Organic‐Free, Lead‐Free, and Dopant‐Free?. Issue 13 (7th October 2019) - Miyasaka, Tsutomu; Kulkarni, Ashish; Kim, Gyu Min; Öz, Senol; Jena, Ajay K.
Abstract: Having demonstrated incredibly fast progress in power conversion efficiency, rising to a level comparable with that of crystalline silicon cells, lead‐based organic–inorganic hybrid perovskite solar cells are now facing the stability tests needed for industrialization. Poor thermal stability (<150 °C) owing to organic constituents and interlayer diffusion of materials (dopants), and environmental incompatibility due to Pb has surged the development of organic‐free, Pb‐free perovskites and dopant‐free hole transport materials (HTMs). The recent rapid increase in efficiency of cells based on inorganic perovskites, crossing 18%, demonstrates the great potential of inorganic perovskites as thermally stable and high‐efficiency cells. Although all kinds of Pb‐free perovskites lag in efficiency in comparison to the hybrid and inorganic perovskites, they also demonstrate better structural and environmental stability. The performance of dopant‐free HTMs matching/surpassing dopant‐containing HTMs makes the former a better choice for stability. Even though the efforts to enhance the stability of Pb‐based hybrid perovskites should continue by different techniques, organic‐free and lead‐free perovskites, and dopant‐free HTMs must be pursued with greater interest for the future. This review describes the present issues and possible strategies to address them, and thus will help to improve the overall performance of robust organic‐free, Pb‐free, and dopant‐free perovskite solar cells. Abstract : Organic‐free (all‐inorganic) and lead‐free halide perovskites in combination with dopant‐free hole transport materials (HTMs) are summarized in terms of potential photovoltaic performance, and progress in compositional and morphological design of solution‐processed perovskite absorbers. Strategies to enhance device efficiency are focused on preparation of high quality perovskite and HTM interface.